Hubungan Rasio Lingkar Pinggang Tinggi Badan (RLPTB) dengan Kejadian Penyakit Hipertensi di Puskesmas Oesapa Kota Kupang NTT - Sadipun Putri Balamangun, Mariel; Lidia, Kartini; Meldy Asa, Halena; Anastasia Deo, Dwita (Riviera Publishing, 2026)
The Waist-to-Height Ratio (WHtR) is one of the measurement tools used to determine central obesity, which is a risk factor for hypertension. However, WHtR has not yet been used in Indonesia as a tool to assess health status. The aim to analyze the correlation between WHtR and the incidence of hypertension at Oesapa Health Center in Kupang City, NTT. The method a cross-sectional study with purposive sampling. The study was conducted on 69 respondents, measuring waist circumference, height, and blood pressure using a measuring tape, microtoise, and digital sphygmomanometer. Data were analyzed using Spearman’s Rho correlation test. Among the respondents, 17.4% (12/69) had a normal WHtR, 47.8% (33/69) had an increased central adiposity WHtR, and 34.8% (24/69) had a high central adiposity WHtR. Additionally, 14.5% (10/69) had normal blood pressure, 26.1% (18/69) were in the prehypertension category, and 59.4% (41/69) had hypertension. The Spearman’s rho test showed a p-value of 0.007 (p<0.05). The Waist-to-Height Ratio (WHtR) is positively correlated with the incidence of hypertension at the Oesapa Health Center in Kupang City.